Contributions of renal water loss and skin water conservation to blood pressure elevation in spontaneously hypertensive rats - Ogura, Takahiro; Kitada, Kento; Morisawa, Norihiko; Fujisawa, Yoshihide; Kidoguchi, Satoshi; Nakano, Daisuke; Kobara, Hideki; Masaki, Tsutomu; Titze, Jens; Nishiyama, Akira (Hypertension Research, 2022)
We recently reported that skin vasoconstriction to suppress transepidermal water loss (TEWL) leads to hypertension in renal injury model rats with impaired urine concentration ability. In this study, we investigated the pathogenesis of hypertension in spontaneously hypertensive rats (SHRs) from the perspective of renal water loss and skin water conservation. We compared the urinary concentration ability, body sodium and water balance, blood pressure, and TEWL in SHRs and control normotensive Wistar-Kyoto rats (WKYs). SHRs showed significantly higher urine volume and lower urinary osmolality than those of WKYs, while there were no significant differences in water intake, urinary osmolyte excretion, and plasma osmolarity between the groups. SHRs exhibited significantly higher blood pressure, skin sodium content, and lower TEWL compared with those is WKYs. Skin vasodilation, induced by elevating body temperature, increased TEWL in both SHRs and WKYs, and significantly reduced blood pressure in SHRs but not WKYs. These findings suggest that physiological adaptation can reduce dermal water loss in SHRs to compensate for renal water loss. Vasoconstriction required for successful cutaneous water conservation explains SHR hypertension. Renal concentration ability and skin barrier function for water conservation may become a novel therapeutic target for essential hypertension.
CRIS-Team WoS Importer:2022-10-28